Outcome evaluation of the Climate, Food and Farming - Global Research Alliance Development Scholarship (CLIFF-GRADS) program - Schuetz, Tonya (2019)
This evaluation assessed the outcomes and preliminary impacts of the CLIFF-GRADS program on enhanced capacity for innovation in partner development organizations. CLIFF-GRADS awards grants to Ph.D. students who are studying low emissions development, with a focus on measurement of greenhouse gas (GHG) emissions from agricultural systems. The goals of the program are to build students’ research skills in the field of greenhouse gas mitigation in agricultural systems, increase their capacities to understand, investigate, and implement low emissions development, and build students’ professional networks in the field of low emissions development. CCAFS invested USD 10,000 per student, 54 students in total over a period of eight years (2011-2018), with 48% women and 52% men participants. The evaluation found that CCAFS support through the CLIFF-GRADS program has been an important capacity development contribution to the graduate students. The CLIFF-GRADS program has had a positive catalytic effect. 31 publications were reported. 80% of respondents applied skills and knowledge from the CLIFF-GRADS program in their work. 71% could initiate new ideas and innovation at their work that made operations more effective. 60% operated new field and laboratory equipment or computer software as a result of the program. 55% built new partnerships. 31% used new or improved research methods. Students indicated that the CGIAR Centers provided strong and skilled support. Some concluding recommendations included, for example, that a clear vision of the results of the CLIFF-GRADS program can strengthen joint efforts by CCAFS and its partners. The role of change agents and champions could be made more explicit during the program.